The Level of satisfaction of the farmers regarding the loan services of San Rafael Rural Bank : an assessment - Dela Cruz, Vermont M.; Yap, Nerissa O.; Isagunde, Lynette R. (Manila : National University, 2000)
The research believe that this study will contribute a lot to the student of banking and finance, the management, the farmers the businessmen, the government, and the Central Bank in the decision making and the people who are willing to gain full in the satisfaction of the farmers regarding the loan services offered by the bank financial institutions.
Title Page -- Approval Sheet -- Acknowledgement -- List of Tables -- Chapter I. The Problem and its Background -- Chapter II. Review of Related Literature -- Chapter III. Research Methodology -- Chapter IV. Presentation, Analysis and Interpretation of Data -- Chapter V. Summary, Conclusion and Recommendation -- Bibliography -- Appendices
Research Method : Descriptive Research Design
Includes bibliographical references.